Studi Deskriptif Awareness dan Persepsi pada Pelaku UMKM dan Koperasi Mengenai SAK EMKM: Sebuah Update - Niluh Putu Dian Rosalina Handayani Narsa; Kadek Pranetha Prananjaya; I Made Narsa (Wahana Riset Akuntansi, 2021)
This study aims to analyze descriptively how the level of awareness of SMEs and cooperatives in East Java Province towards SAK EMKM. After that, it will also be analyzed how the perception of MSME actors and cooperatives regarding the usefulness and unutility of SAK EMKM. Data collection methods using questionnaires and research subjects as many as 90 respondents. The results showed that 47.8% of respondents knew about SAK EMKM and only 14.9% of respondents had good knowledge of SAK EMKM. The perception of usefulness that financial statements can be more easily understood if made based on SAK EMKM becomes the perception with the highest average while the perception of the number of disclosures that must be made by the entity becomes the perception of uselessness with the highest average. Although this research is only in the form of descriptive quantitative analysis and does not test a hypothesis, this research is expected to increase our insight and knowledge, especially to parties with an interest in SAK EMKM, especially since there has been no research that has tried to examine this comprehensively. Keywords: Cooperative’s Subject; SAK EMKM; SAK ETAP; SME’s Subject.